2018
DOI: 10.3390/app8050825
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Diesel/LPG Dual Fuel on Performance and Emissions in a Single Cylinder Diesel Generator

Abstract: Compared to other engines of the same size, diesel engines are more economical in addition to their ability to generate high power. For this reason, they are widely used in many fields such as industry, agriculture, transportation, electricity generation. The increasing environmental concerns and diminishing oil resources led researchers to improve fuel consumption and emissions. In this context, the usage of Liquefied Petroleum Gas (LPG) fuel in diesel engines is one of the important research subjects that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 39 publications
2
13
0
2
Order By: Relevance
“…Using two fuels significantly increased the emissions of CO (by about 24 times) and HC (by about 28 times), but the NOx volume decreased by 67-82%, and the smoke emitted by the engine decreased by 23- Research on the use of LPG fuel in internal combustion engines shows different conclusions as to the effects of their application. The authors of [34] presented the results of tests of a compression-ignition internal combustion engine (cylinder capacity 296 cm 3 and 5.59 kW) powered by two types of fuel (diesel and LPG in different ratios), showing that the use of LPG injected in the liquid phase to the fuel may reduce CO and HC emissions by about 20-30% and increase NO x emissions by 6% [34]. A comparative study of the energy and ecological parameters of dual-fuel engines (diesel-natural gas (NG) and hydrotreated vegetable oil (HVO)-biogas) and conventional diesel oil in a compression-ignition engine showed that the use of methane in the dual-fuel mixture reduced the CO 2 volume in the exhaust by 17-20%, and biomethane increased the CO 2 volume by 10-14%.…”
Section: Introductionmentioning
confidence: 99%
“…Using two fuels significantly increased the emissions of CO (by about 24 times) and HC (by about 28 times), but the NOx volume decreased by 67-82%, and the smoke emitted by the engine decreased by 23- Research on the use of LPG fuel in internal combustion engines shows different conclusions as to the effects of their application. The authors of [34] presented the results of tests of a compression-ignition internal combustion engine (cylinder capacity 296 cm 3 and 5.59 kW) powered by two types of fuel (diesel and LPG in different ratios), showing that the use of LPG injected in the liquid phase to the fuel may reduce CO and HC emissions by about 20-30% and increase NO x emissions by 6% [34]. A comparative study of the energy and ecological parameters of dual-fuel engines (diesel-natural gas (NG) and hydrotreated vegetable oil (HVO)-biogas) and conventional diesel oil in a compression-ignition engine showed that the use of methane in the dual-fuel mixture reduced the CO 2 volume in the exhaust by 17-20%, and biomethane increased the CO 2 volume by 10-14%.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their advantages, diesel engines can have faultsmost especially with energy transfer. As seen clearly in literature, diesel engines only transfer40% of the total energy into useful work [1][2][3]. The internal combustion (IC) engine's energy is exhausted in 3 sections; energy used by the cooling liquid, energy used in attaining useful work and energy loss via the exhaust.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies on diesel engines to boost engine efficiency and reduce harmful emissions by using alternative fuels. Exhaust emissions from the CI engine are harmful to our respiratory system, and also effective on environment pollution [4,[6][7][8][9][10][11][12][13][14]. In addition to engine parameters, the emission depends on the combustion process and the chemistry used for the fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental tests were performed on a single-cylinder water-cooled ignition compression engine operating in dual-fuel mode with diesel as pilot fuel and LPG as the main fuel. The engine was run under different operating conditions and for the best efficiency, the optimal combination of the proportions induced to inject fuel energy is calculated in each case [8,27,28].…”
Section: Introductionmentioning
confidence: 99%